Morphological variations in cadmium sulfide nanocrystals without phase transformation (2011)
ABSTRACT: A very novel phenomenon of morphological variations of cadmium sulfide (CdS) nanorods under the transmission electron microscopy (TEM) beam was observed without structural phase transformation. Environmentally stable and highly crystalline CdS nanorods have been obtained via a chemical bath method. The energy of the TEM beam is believed to have a significant influence on CdS nanorods and may melt and transform them into smaller nanowires. Morphological variations without structural phase transformation are confirmed by recording selected area electron diffraction at various stages. The prepared CdS nanorods have been characterized by X-ray powder diffraction, TEM, UV-Vis spectroscopy, and photoluminescence spectroscopy. The importance of this phenomenon is vital for the potential application for CdS such as smart materials.